Synthesis and characterization of the mer-[RuCl3(NO)(dppb)] isomer. X-ray structures of fac-[RuCl3(NO)(dppm)], cis-[RuCl2(dppm)2] and mer-[RuCl3(NO)(dppb)] [dppm=1,2-Bis(diphenylphosphino)methane and dppb=1,4-Bis(diphenylphosphino)butane] - Batista, Alzir A.; Pereira, Cid; Wohnrath, Karen [UNESP]; Queiroz, Salete L.; De A. Santos, Regina H.; Do P. Gambardella, Maria Teresa (Elsevier, 1999)
The fac-[RuCl3(NO)(dppm)] (1) and cis-[RuCl2(dppm)2] (2) complexes were obtained with co-crystallization in the solid state from the reaction of RuCl3(NO) with the diphosphine in dichloromethane. mer-[RuCl3(NO)(dppb)] (3) was obtained from [RuCl3(dppb)(H2O)] by bubbling NO for 30 min in the same solvent. The crystal and molecular structures of these three compounds have been determined from X-ray studies. © Elsevier Science Ltd.
Keywords: Complexes, Biphosphines; Isomerism; Nitrosyl; Ruthenium; X-ray structure